New record of middle jurassic radiolarians and evidence of neotethyan dynamics documented in a melange from the central dinaridic ophiolite belt (CDOB, NE Bosnia and Herzegovina) - Segvic, Branimir; Kuko, Duje; Dragievi, Ivan; Vranjkovi, Alan; Bri, Vlatko; Gorian, Špela; Babaji, Elvir; Hrvatovi, Hazim (Ofioliti, 2014)
Within the ophiolitic mélange of the Central Dinaridic Ophiolitic Belt (CDOB) that stretches throughout the Balkans region in SE Europe, a latest Bajocian-early Bathonian radiolarian assemblage was obtained from chert-rich shaly to silty matrix. The sampling locality in northern Bosnia and Herzegovina is characterized by a highly-diversified ophiolitic suite, consisting of basic and ultrabasic rocks of different geotectonic provenances. This makes the radiolarian dating a convenient complementary tool for studying the geodynamic history of CDOB within a broader regional context. The host sediments and the nature of their associated crystalline rocks suggest that radiolarian deposition occurred relatively close to the Adria shelf margins, predating or being contemporaneous to the rapid transitions in the Dinaridic Neotethys geotectonic setting, changing from active ridge magmatism to an intraoceanic subduction environment and island-arc volcanism. The minimum age of ophiolite mélange formation is defined by the mineral equilibration ages in metamorphic sole (161±4 Ma), with the obduction tectonics that must have lasted at least until the Oxfordian time (i.e. termination of MOR activity in the Dinarides). This age correlates well with the ages of sediments reported elsewhere in the mélange of the Dinaride-Hellenide orogenic system.